Carriage of Internationally Spread Clones ofStreptococcus pneumoniaewith Unusual Drug Resistance Patterns in Children Attending Day Care Centers in Lisbon, Portugal - Raquel Sá‐Leão; Alexander Tomasz; Ilda Santos‐Sanches; António Brito‐Avô; Sigurdur E. Vilhelmsson; Karl G. Kristinsson; Hermı́nia de Lencastre (2000)
Over half (259/503) of drug-resistant (DR) pneumococci colonizing healthy children attending day care centers in Lisbon were identified by molecular typing methods as representatives of several internationally spread clones. These included the 2 penicillin-resistant pandemic Spanish/USA and French/Spanish clones (21% of all DR pneumococci) and 5 new lineages with unusual antibiotypes (accounting for an additional 30% of all DR pneumococci). The most characteristic feature of the latter group was the high frequency of resistance to macrolides and tetracycline and very low or no resistance to penicillin. These observations provide support for the notion that the nasopharyngeal flora of children in day care centers may be a global reservoir of worldwide prevalent strains of DR pneumococci.